Differentiated Learning in Reading Comprehension in Class V - Chilviana, Tena; Iswara, Prana Dwija (International Conference on Elementary Education, 2025)
The purpose of this study is to define the influence of differentiated learning strategies in reading comprehension learning in fifth-grade. This research was carried out in one of the State Elementary Schools in Garut Regency with the number of students in class V as many as 32 people. The research method used is qualitative descriptive. At the beginning of the meeting, data was obtained that only 9 out of 32 students or 28% were able to read with clear pronunciation and intonation according to punctuation and understand the content of the reading and retelling, the rest were 23 students or 72% who had not mastered the information from the books they read. Researchers using differentiated learning strategies can improve students’ reading comprehension skills. The differentiation strategy used is to differentiate students’ learning readiness in reading comprehension by mapping the learning needs of students in reading comprehension, then choosing reading materials by learning needs of students. The results of the study showed a significant improvement obtained after implementing differentiated learning strategies. As a result of this activity, data was obtained as many 30 students who were able to rewrite the content of the readings they read and only 2 of the students were not able to rewrite what they read.